Prevention of radioactive pollution: A comparative simulation study on the reduction of several important radionuclides by pyrite and magnetite - Yu, Haoqi; Yu, Tao; Zeng, Kai (Frontiers in Environmental Science, 2022)
After a long-term storage, disposal tanks and engineering barriers will eventually be damaged due to aging, which will further cause the migration of the radionuclides by groundwater into the surrounding rock medium. However, in order to ensure the long-tern effective isolation of radionuclides from the human being environment, pyrite and magnetite that exist widely and stably in geological environment can be used to ensure the strong mobility of high valence redox sensitive nuclides to the low mobility nuclides in order to prevent the strong migration of radionuclides released to the biosphere. In this work, the reducing reaction between the pyrite, magnetite and redox-sensitive radionuclides (U, Se, Tc and Np) in the Gansu proposed-treatment plants area were under the simulation by the PHREEQC using the THERMOCHIMIE-TDB 10a database from the ANDRA/RWM of France and also calculated its corresponding precipitation saturation index and species. The results suggested that pyrite can significantly reduce the valence of high-valence radionuclides (U, Se, Tc and Np). However, magnetite in a given condition showed a certain reducing effect against Se and Np and a poor effect of U and Tc. These conclusions have an important guiding significance for the prevention and retention of radioactive pollution released to the biological environment.